Emotional Manipulation in Cyberspace: Examining Digital Deception's Consequences on Intimacy and Trust - Gibbs, Tiphanie (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The growing digital communication has opened new avenues for emotional manipulation and deception to occur in personal relationships, especially within the context of marriage. This study aimed to investigate the online practices that best exemplify these negative relational dynamics—catfishing, digital infidelity, and emotional blackmail. It examines the impact of these practices on trust and intimacy. To understand the situation, we conducted two parts of research—one quantitative, the other qualitative. The digital deceptions we found are causing significant emotional distress in those being deceived, making them feel (a) excessively anxious, (b) unduly depressed, and (c) dangerously low in self-trust. They also give rise to relational power dynamics that seem far more imbalanced than the traditional marital roles of husband and wife would suggest. Furthermore, through various cyberpsychological frameworks, we've utilized, it is apparent that these enacted deceptions also cause more relation between the deceivers and those being deceived.